The Effectiveness of STEAM-Based Learning on Vocational Students’ Creative Thinking Skills and Self-Efficacy in Linear Equations - Agil Dwijayanti; Rosiatuningsih Rosiatuningsih; Mahdia Silmi Aziz; Norma Rahmalia Ayuwanda; Gunawan Gunawan; Eng Tek Ong (IJECA (International Journal of Education and Curriculum Application), 2026)
The development of 21st-century competencies requires mathematics learning that fosters not only conceptual understanding but also creative thinking skills and self-efficacy. However, these competencies are often underdeveloped in vocational high schools due to teacher-centered learning approaches. This study examines the effectiveness of STEAM-based Project-Based Learning (PjBL) on students' creative thinking skills and self-efficacy in learning systems of linear equations in two variables. A quasi-experimental pretest–posttest control group design was employed involving 60 tenth-grade students from the Visual Communication Design (DKV) program. The experimental group received STEAM-based PjBL, while the control group received conventional PjBL. Creative thinking skills were measured using essay tests (fluency, flexibility, originality, elaboration) and self-efficacy via a Likert-scale questionnaire, both validated through expert judgment with Cronbach's alpha of 0.76 and 0.87. Data were analyzed using Pearson correlation and MANCOVA. The experimental group outperformed the control group in creative thinking (M = 86.50, SD = 3.72 vs. M = 75.27, SD = 3.25; N-Gain = 0.65 vs. 0.36, medium category) and self-efficacy (M = 88.00, SD = 2.56 vs. M = 76.93, SD = 2.96; N-Gain = 0.33 vs. 0.19, moderate vs. low category). MANCOVA confirmed a significant simultaneous effect (Wilks' Lambda = 0.010, p < 0.05, η² = 0.990), and a very strong correlation between both variables (r = 0.978, p < 0.01). These findings confirm that STEAM+PjBL provides meaningful, contextual, and interdisciplinary learning experiences that simultaneously enhance creativity and self-confidence, and is recommended as an innovative instructional strategy in vocational mathematics education.